Resilience, Secular attitude and Forgiveness among indian men & women - Mahesh Kore; Dr. Bharat Naik (International Journal of Behavioral Sciences, 2026)
The present study investigates the relationship among forgiveness, resilience, and secular attitude among adults living in Pune, India. The primary objectives of the study were to examine the interrelationship between these three variables, evaluate the influence of secular attitude on forgiveness and resilience, and identify differences based on gender and region. 113 adults were selected through a simple random sampling method and were assessed using the Bharathiar University Resilience Scale (BURS), the Heartland Forgiveness Scale (HFS), and the Secular Attitude Scale (SAS). The collected data were analyzed using descriptive statistics and Pearson correlation analysis. The findings revealed that individuals with higher secular attitudes also demonstrated higher levels of forgiveness and resilience. Female participants showed comparatively greater resilience than male participants did, while participants from rural areas were found to be more resilient than those from urban regions. Overall, the study emphasizes the importance of secular values in promoting forgiveness and resilience, which play a significant role in enhancing psychological well-being and maintaining social harmony. These findings further suggest that fostering secular outlooks through education and community programs may strengthen adaptive coping mechanisms, reduce interpersonal conflicts, and encourage inclusive attitudes among individuals across diverse sociocultural backgrounds in rapidly changing contemporary society in present times globally.
Keywords: Social Harmony; adults; forgiveness; gender; psychological well-being; resilience; secular attitude